EVALUASI KUALITAS AIR SUNGAI BAWAH TANAH SEROPAN SEBAGAI SUMBER AIR MINUM PERUSAHAAN DAERAH AIR MINUM (PDAM) SUB SISTEM SEROPAN KABUPATEN GUNUNGKIDUL - , TITIS WISNUWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The good water supply in quatity is able to supply the water that adequate for society in equitable and ensured susteinability, while in quality is the water fulfill the healty requirements. PDAM is a enterprise that was established management program of the drinking water. One of them is dringking water problem faced every year especially during the rainy season. The real condition is the water be turbid at rainy season in PDAM distribution network of Seropan Sub Sistem in Gunungkidul Regency. The puposes of these research are to determined suitability the quality of water drinking and to know alteration the quity of drinking water from Seropan Underground River to PDAM consumer pipes of Seropan Sub Sitem especially at rainy season. Survey method in these research emphasize of direct field survey. The primary data is water samples which is determined by purposive sampling and the collecting water samples conduct in intake, reservoir, and consumer pipes for examined in laboratory. Parameter water quality that measured is physic, chemistry, and biologic parameters of water quality. The final analysis that used is graphically analysis, qualitative descriptive analysis and spatial anlysis. The result showed that analysis PDAM drinking water quality result there is exceed the standard water quality based on Minister of Health of Republic Indonesia regulation number 907/MENKES/SK/VII/2002, namely color, turbidity, and total coliform. Water quality from Seropan Underground River as prime source until consumer pipes at rainy season has very change. Increase and decrease of chemical parameters are still meet to the water quality ambient and does not affect to the chemical reactions during the distribution process through the pipes.